Piezoelectric force sensors for hexapod transportation platform - Luneckas, Mindaugas; Luneckas, Tomas; Gavelis, Vytenis; Valaitis, Vytautas; Udris, Dainius (Transport, 2015)
Rough terrain is one of the major issues for transporting various objects to different remote locations. Wheeled platforms or robots are not suitable for such tasks due to a lack of ground clearance. Walking robots, despite their slower speed, can be successfully used as transportation platforms that can overcome the environment. However, leg placing requires accurate supervision and the force sensing system must be developed on each foot to acquire equal force distribution between legs and to obtain stable motion over the irregular surface. In this paper, we investigate the improvement of the hexapod robot’s feet by upgrading them with piezoelectric force sensors. By monitoring force dependence on transferred legs, we establish the most suitable hexapod gait for moving over the even surface.